How Long Has the Earth Existed? Persuasion and World‐Picture in Wittgenstein's On Certainty. (20th May 2015) - Perissinotto, Luigi
Abstract: In some sections of On Certainty, Wittgenstein uses the term "persuasion, " pitting it, on the one hand, against "giving reasons" (proving and justifying), and comparing it, on the other, to conversion (also in the religious sense of the term), while, finally, defining it as "giving someone one's own picture of the world." In this essay, I analyse these sections, in an effort to fit them into the broader context of On Certainty, and to clarify the meaning and the limits of the comparison between persuasion and conversion. My aim is to show that persuasion as Wittgenstein understands it here is quite similar to what we could call "re‐education."